Best Answer

x2 + 10x = 0

x2 + 10x + 25 = 25

(x + 5)2 = 25

x + 5 = +-5

x1 = 0

x2 =10

Q: How do you answer the problem x2 plus 10x plus equals 0?

Write your answer...

Submit

Still have questions?

Continue Learning about Other Math

x2 + 9 = 10x x2 - 10x + 9 = 0. (x - 9)(x - 1) = 0. Therefore, x = 1 or 9.

x2 - 10x + 25 = 0(x - 5)(x - 5) = 0x - 5 = 0x = 5

When x = -5

Given: x2 + y2 - 10x + 4y + 4 = 0 First, we'll move our constants to the right: x2 + y2 - 10x + 4y = -4 Then group terms with the same variables together: x2 - 10x + y2 + 4y = -4 Then complete the squares: x2 - 10x + 25 + y2 + 4y + 4 = -4 + 25 + 4 (x - 5)2 + (y + 2)2 = 25 And there we have it. This is an equation for a circle whose center point is at (5, -2), with a radius of √25, which equals 5.

X2 + 8x + 16 = 10x +16x2 + 8x + 16=2x + 8x + 16=10x + 16

Related questions

x2 + 10x + 21 = (x + 3)(x + 7)

x2 + 9 = 10x x2 - 10x + 9 = 0. (x - 9)(x - 1) = 0. Therefore, x = 1 or 9.

For a start you tell us what the expression equals....

x = -3.27 or -6.73

-6

-2-5

Twenty-Five x2 + 10x = 8 x2 + 10x + 25 = 8 + 25 (x + 5)2 = 33

x2+10x+1 = -12+2x x2+10x-2x+1+12 = 0 x2+8x+13 = 0 Solving by using the quadratic equation formula: x = - 4 - or + the square root of 3

x2 - 10x + 25 = 0(x - 5)(x - 5) = 0x - 5 = 0x = 5

(x + 8)(x + 2)

x2+10x-336

x2+10x+1 = -12+2x x2+8x+13 = 0 The solution: x = -4 + the square root of 3 or x = -4 - the square root of 3